The problem of communication in education - Mihaleva, Nikoleta (Advances in Social Sciences Research Journal, 2021)
The article considers the connection of education with teaching as a mean for its realization and the new type of socio-historical inheritance at the end of the XX century. This is related to the changes in the nature of scientific knowledge itself, with the understanding that education is a complicated complex in which, along with teaching, education is present as a process of cooperation and co-creation between teachers and students. And this, in turn, raises the question of changes in value attitudes ​​and new cultural realities in the process of communication / so far understood narrow-mindedly as a converse /, which builds a new type of holistic personalities, whose mentality unites culture and education.